Quality of Accountancy graduates produced by the Nanyang Technological University Singapore. - Fong, Daniel Pin Jan. (2008)
This study endeavours to assess the perceived quality of the accountancy graduates currently produced by NTU, with the ultimate aim of developing an instrument that enables the university to measure the quality, from the employers' viewpoint, of the accountancy graduates produced. The research also aims to identify areas for improvements, in terms of the desired qualities and characteristics that employers expect fresh graduates to have, but are deemed to be lacking.